Ukuran Perusahaan Dan Profitabilitas Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening Pada Perusahaan LQ45 - Nadhiya Maharany; Sri Sudarsi (Warmadewa Management and Business Journal (WMBJ), 2026)
This study aims to examine the effect of firm size and profitability on firm value with capital structure as an intervening variable in LQ45 companies listed on the Indonesia Stock Exchange (IDX) during the 2022– 2024 period. This research employs a quantitative approach using secondary data obtained from companies’ financial statements. The research sample was selected using a purposive sampling method, resulting in companies that met the predetermined criteria during the observation period. The data analysis techniques used include multiple linear regression analysis and path analysis to test both direct and indirect effects among variables. The results indicate that profitability has a positive and significant effect on firm value, while firm size does not have a significant direct effect on firm value. Furthermore, profitability and firm size are proven to have a positive and significant effect on capital structure. Capital structure also has a positive and significant effect on firm value. In addition, the findings reveal that capital structure is able to mediate the effect of profitability and firm size on firm value. These results suggest that optimal capital structure management plays an important role in enhancing firm value, particularly in LQ45 companies.